Integrating tissue dosimetry and mode of action to evaluate atrazine dose-response - McMullin, Tami S., author; Hanneman, William H., advisor; Handa, Robert J., committee member; Clay, Colin M., committee member; Legare, Marie E., committee member; Andersen, Melvin E., committee member (Colorado State University. Libraries, 2005)
Atrazine (ATRA) is a widely used chlorotriazine herbicide that causes neuroendocrine effects in animal toxicity studies. Such effects include suppression of the LH surge in estrogen primed female, ovariectomized rats treated with high doses of ATRA. While the mechanism by which ATRA alters neuroendocrine function is not known, previous studies indicated that ATRA had anti-estrogenic properties in vitro and in vivo. In addition, ATRA is metabolized to chlorinated metabolites by P450 mediated saturable to oxidative metabolism and to non-chlorinated metabolites by GST-mediated GSH conjugation. Accurate determination of the risk of ATRA to exposed human populations is limited by uncertainties in extrapolating the dose-response behavior of a compound using animal toxicity data to predict responses in humans. Knowledge of tissue dosimetry (i.e., the tissue concentrations of ATRA and/or Cl-TRI metabolites that produce neuroendocrine responses) and mode of action (i.e., how ATRA and/or its metabolites interact with tissue constituents to cause these responses), is especially important for determining risk posed by ATRA exposure. The studies presented in this dissertation examined the anti-estrogenic mode of action of ATRA and DACT in brain and the processes that control the kinetic disposition of ATRA and its metabolites in plasma and target tissue (the brain) under conditions that cause LH surge suppression. A series of pharmacokinetic models were developed to describe in vitro and in vivo kinetic data on ATRA and its metabolites. The time-course concentrations of A TRA and the chlorinated metabolites in plasma and brain were regulated by dose-dependent and sequential absorption of compound from gut, oxidative metabolism in the liver and intestine, reactivity with hemoglobin in red blood cells and with plasma proteins, systemic clearance by GST mediated GSH conjugation and urinary elimination. These processes resulted in minimal concentrations of A TRA and retention of the mono-dealkylated metabolites and DACT in plasma and brain. DACT was the major chlorotriazine present in tissue, representing over 95% of total chlorotriazine area under the concentration curve after dosing with ATRA. In evaluating the neuroendocrine mode of action of Cl-TRIs, we determined that ATRA and DACT suppress the LH surge by mechanisms other than altering binding of estrogen to its cognate receptors in the hypothalamus. Moreover, pituitary responsiveness was altered in animals treated with concentrations of DACT that suppressed the estradiol/progesterone induced LH surge. The high degree of reactivity of DACT with sulfhydryl residues in rat hemoglobin indicate that tissue reactivity of DACT should be considered as a possible mode of action rather than direct interaction, either inhibition or activation, with cellular receptor molecules. These present studies have improved our understanding of the mechanisms by which chlorotriazines alter the LH surge and the factors that control chlorotriazine tissue dose under conditions where neuroendocrine responses are observed. As such, these studies should assist low-dose, and to some extent, inter-species extrapolations of the dose-response behavior of chlorotriazines. This research has also identified additional mode of action and kinetic studies that will be required to create a complete model that describes the kinetic and biological effects to support low dose and interspecies extrapolation of risks in humans posed by ATRA.
Keywords: toxicology